A passion for China : Norwegian mission to China until 1949 - Engelsviken, Tormod; Thelle, Notto R., 1941-; Larsen, Knut Edvard, 1960- (Regnum studies in mission., 2015)
"Protestant Western mission to China since Robert Morrison arrived in Macao in 1807 until Mao Zedong's Communist revolution 1949 has been controversial, not least in China. When the missionaries after 1949 were expelled from China, the official Chinese history did not leave them much honour. They were viewed as lackeys of Western imperialism propagating a religion that was "feudal superstition" and which would eventually disappear in a Communist society. Yet, today the view of the missionaries is changing in Chinese historiography. This book is an attempt to present some aspects of the many-faceted Norwegian Protestant mission to China during the 60 years from about 1890 to 1949. Among the themes that are dealt with in the ten chapters are the background of missionaries and their motivation for mission to China, the personal relationship between the missionaries and the Chinese, missionary contributions to contextual Chinese preaching, liturgy and hymns, missionaries as instruments of revival, and social justice and women's rights. The book is also a tribute to all the men and women who gave their lives to the mission to China and to the millions of Christians of China who have persevered during hard times until today."--Publisher